AUDIT INTERNAL AKTIVA TETAP PADA DINAS SOSIAL PROVINSI KALIMANTAN TIMUR - Rosnita, Ayu Erlinda (EKONOMIA, 2012)
Financial statements prepared in particular the East Kalimantan provincial government of East Kalimantan Social Service is a structured report on the financial position and transactions carried out by a reporting entity. Fixed assets held by the Social Service of East Kalimantan really exist and was validated. No fixed assets were used as collateral for loans and have been presented in the list of fixed assets, fixed assets owned and used by the agency assessed based on the actual cost, so that the judgment does not deviate from the Government Accounting Standards.